2008
DOI: 10.1111/j.1444-2906.2008.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of Nibea albiflora in Yellow Sea and East China Sea

Abstract: The population genetic structure and level of gene flow of Nibea albiflora from the Yellow Sea and the East China Sea were examined with a 479-bp segment of a mtDNA control region. In total, 65 samples were collected from three locations and 37 haplotypes were obtained. Mean haplotype diversity and nucleotide diversity for the three populations ranged from 0.9130 Ϯ 0.0308 (Zhoushan) to 0.9926 Ϯ 0.0230 (Xiamen), and from 0.0073 Ϯ 0.0043 (Qingdao) to 0.0099 Ϯ 0.0057 (Xiamen). Analysis of molecular variance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…Generally, marine fishes are considered to have a low level of genetic differentiation among different geographic populations because of the high dispersal capabilities, large population sizes and relatively small barriers in the marine environment (Beheregaray and Sunnucks, 2001 difference in the population genetic structure between the Yellow Sea and East China Sea observed using mtDNA (Han et al, 2008). For the shrimp Fenneropenaeus chinensis, no significant population genetic differentiation between the Yellow Sea and Bohai Sea was found using both microsatellite DNA and mtDNA (Liu et al, 2006;Li et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, marine fishes are considered to have a low level of genetic differentiation among different geographic populations because of the high dispersal capabilities, large population sizes and relatively small barriers in the marine environment (Beheregaray and Sunnucks, 2001 difference in the population genetic structure between the Yellow Sea and East China Sea observed using mtDNA (Han et al, 2008). For the shrimp Fenneropenaeus chinensis, no significant population genetic differentiation between the Yellow Sea and Bohai Sea was found using both microsatellite DNA and mtDNA (Liu et al, 2006;Li et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Pelagic marine fi shes were expected to show low levels of genetic differentiation in different regions because of their higher dispersal potential during the planktonic egg, larval or adult history stages coupled with an absence of physical barriers between the ocean basin and adjacent continental margins (Yu et al, 2002;Cabranes et al, 2008;Han et al, 2008). Although adult Japanese fl ounder are relatively sedentary, their larvae and juveniles are regarded as being pelagic for more than a month (Zhang et al, 1965).…”
Section: Genetic Differentiation Between the Two Populationsmentioning
confidence: 98%
“…In general genetic homogeneity in marine fishes can be attributed to high dispersal potential during the planktonic egg and larval stages coupled with an absence of physical barriers between ocean basins and adjacent continental margins. Previous studies have revealed that the ocean currents in the China Sea facilitate the dispersal of marine larvae among distant populations (Han et al, 2008;Shui et al, 2009;Xiao et al, 2009). Data analysis from the COI gene sequences revealed genetic heterogeneity in E. tetradactylum populations in 51, 57, 61 and 71 FAO fishing areas.…”
Section: Tests Of Neutrality and Population Expansion Estimationmentioning
confidence: 99%